Analisis Kesehatan Koperasi Syariah dalam Upaya Meningkatkan Kinerja dan Pelayanan : Studi Kasus BMT-UGT Sidogiri Cabang Balung, Kab. Jember - Huda, Miftahul; Yulinartati,; Suharsono, Riyanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Cooperatives are the largest number of financing businesses in the country. In addition to the number, there are also various types of cooperatives, namely savings and loans cooperatives, all-business cooperatives, village unit cooperatives, and many others. There are also cooperatives that also combine conventional cooperative principles with sharia cooperative principles. The purpose of this study is to prove and examine the impact of financial performance on service quality and with the health condition of cooperatives at BMT-UGT Sidogiri Balung Branch, Jember. This research applies quantitative descriptive methods and uses a descriptive approach. The object in this study is Baitul maal wat Tanwil (BMT) UGT Sidogiri Balung Branch, Jember. The results of research that has been carried out on the analysis of the health level of savings and loans cooperatives and sharia financing of BMT-UGT Sidogiri Balung Branch since 2021 can be said to be in the category of healthy cooperatives.